2014
DOI: 10.1186/1471-2393-14-25
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of severe maternal morbidity and near miss and associated factors in Sergipe, Northeast Brazil

Abstract: BackgroundThe investigation of severe maternal morbidity (SAMM) and maternal near miss (NM) and associated risk factors is important for the global reduction of maternal mortality. This study investigated the prevalence of SAMM and NM cases and the associated risk factors in two reference maternity hospitals in a capital city in Northeast-Brazil.MethodsA cross-sectional study with a nested case–control component was conducted from June-2011 to May-2012. Case identification was prospective and data collection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
55
2
24

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 17 publications
11
55
2
24
Order By: Relevance
“…In this study, the maternal mortality rate, the incidence rate of MNM and the ratio of MNM: MD were similar to those identified in a study carried out two years ago in Sergipe (6) , which indicates that the reduction in the number of maternal deaths and NM is a slow process, requiring consistent and active public policies, coupled with constant quality surveillance. However, although the results are lower than those recommended by the WHO, they are better compared to those of some countries such as Palestine, Lebanon, Egypt and Syria, in which one study observed a higher prevalence of MNM and MD (7) .…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the maternal mortality rate, the incidence rate of MNM and the ratio of MNM: MD were similar to those identified in a study carried out two years ago in Sergipe (6) , which indicates that the reduction in the number of maternal deaths and NM is a slow process, requiring consistent and active public policies, coupled with constant quality surveillance. However, although the results are lower than those recommended by the WHO, they are better compared to those of some countries such as Palestine, Lebanon, Egypt and Syria, in which one study observed a higher prevalence of MNM and MD (7) .…”
Section: Discussionsupporting
confidence: 84%
“…60 Souza et al 9 and Galvão et al 22 studies found an association between previous abortion and maternal near miss, and Santana et al 37 and Camargo et al 51 studies reported a higher risk of near miss in women submitted to abortion.…”
Section: Discussionmentioning
confidence: 99%
“…61 In several studies, previous or current cesarean section was associated to MNM/ESMM/SMM. 21,22,24,25,27,29,34,52 Only one study showed cesarean section as a protective factor. 17 The maternal near miss rate for cesarean section was 91 cases/1,000 deliveries whereas the incidence rate on vaginal delivery was 16 /1,000 deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…They found anemia (55%) and previous cesarean section (45%) to be the most common associated conditions with severe maternal morbidity. In a crosssectional study with a nested case-control component, Galvão et al (10) found the maternal near miss ratio to be 5.8 cases/1,000 live births. In the multivariate analysis, patient's status, previous caesarian, abortion and level of consciousness were reported as significant (10).…”
Section: Discussionmentioning
confidence: 99%